Family Support in Effort Reduce Hospitalization Reaction in Children of Preschool in Anggrek Room Nganjuk Hospital - Risa Nurhayati; Indasah Indasah; Byba Melda Suhita (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2018)
Disease and hospitalization are often the main crises that children face, causing the child to experience trauma. The phenomenon of separation and experience of hospitalized children shows when a child is hospitalized will experience a change in emotional status, as well as parents crying, anxious, angry. Preschool age is very susceptible to the effects of tress during hospitalization, so there is a need for family support. The objective of the study was to explore the support of the family in order to decrease the hospitalization of preschool children in the orchid room of RSUD Nganjuk. The research method used qualitative research with phenomenological approach. Data collection using primary and secondary data then conducted in-depth interviews (indepth interview) with semi-structured questions. Informants as many as 5 people according to the inclusion criteria that researchers make are families who have preschool children, long day 1-3 care, family as the main caregiver, children with medical diagnosis group of internal medicine, children do not have terminal disease, the family is willing to become informants. The results show that family support includes informational support, assessment support, emotional support and instrumental support. But the support has not been maximal because it is influenced by the reaction of children and parents who are varied towards hospitalization along with influencing factors such as child adaptation process, the existence of rooming in, sibling reaction. The conclusion of the study was family support during the effort to decrease the hospitalization reactions of preschool children. Based on these studies it is necessary to conduct further research on family support in reducing the impact of pre-school children's hospitalization.